Effects of gonadectomy on clinical-hematological, metabolic and hormone conditions of cockerels - ZakharenkoМ. О.; CheverdaІ. М.; KurbatovaІ. М. (Regulatory Mechanisms in Biosystems, 2022)
Gonadectomy (caponization) of cockerels is an important way of increasing their productivity, improving the quality and taste properties of the meat, and obtaining dietary products. The objective of the study was the influence of gonadectomy of cockerels on their clinical condition, morphological composition of blood, hemoglobin content and anabolism in the tissues, their productivity and chemical content of the muscles. In the experiment, we used 30 Adler silver cockerels aged 4 weeks, which were divided into two groups: control (intact) and experimental (gonadectomized) according to the analogue principle, with 15 individuals in each. The experiment lasted for 185 days, including the main period of 175 days. We determined that the body temperature of cockerels after gonadectomy increased as early as days one and three. In the blood of gonadectomized cockerels, the number of leukocytes decreased by 36.3%, thrombocytes – by 24.7%, while hemoglobin concentration, numbers of heterophils, eosinophils, basophils, monocytes and lymphocytes did not change compared with the intact individuals. On days 20 and 185 of the experiment, the concentration of testosterone in the blood plasma of gonadectomized cockerels was lower respectively by 57.1% and 53.1%, whereas no differences were found prior to gonadectomy and on the third day of the experiment. We determined increase in uric acid concentration and decrease in the level of ionizing calcium in blood plasma of gonadectomized cockerels compared with intact individuals, while the content of cortisol, glucose, total protein, triglycerides, cholesterol, total calcium and inorganic phosphorus, and also activities of alkaline phosphatase, alanine aminotransferase and aspartate aminotransferase did not change. Live weight of gonadectomized cockerels in the period from 45 to 105 days of the raising did not change, and was higher by 10.4–17.0% from day 115 to 145, and further remained not different from the control. Thoracic muscles of gonadectomized cockerels contained 1.8 times more fat, while the levels of moisture, dry matter, protein and ash in thoracic and thigh muscles did not change. The conducted studies have revealed the effect of gonadectomy of roosters on clinical-hematological parameters, metabolic processes, productivity of birds and chemical composition of muscles and may be used to improve the production of chicken meat with high dietary and taste properties.